Composition and Structure of the Entomofauna of Ferula (Ferula kuhistanica) in Different Sections of the Zarafshan Ridge (Journal of the Entomological Research Society, 2023)
The article analysis the species composition of the entomofauna of the Kuhistan ferula (Ferula kuhistanica) in different parts of the Zarafshan ridge. The study revealed 115 species of insects belonging to 92 genera, 48 families, and eight orders. The identified species belong to the following orders: Thysanoptera (1 species), Neuroptera (3 species), Homoptera (1 species), Hemiptera (17 species), Coleoptera (36 species), Lepidoptera (5 species), Hymenoptera (14 species) and Diptera (38 species). By the nature of the relationship with the ferula, the entomofauna is divided into six ecological groups. Phytophages, including four ecological groups, accounted for 36.5% (42 species), pollinators 49.6% (57 species) and entomophagous 13.9% (16 species). A comparative analysis of the diversity of entomofauna in different parts of the Zeravshan Range was carried out, and a dendrogram of the similarity of the entomofauna of the studied territories was compiled. The horizontal and vertical isolation of the entomofauna was revealed. The most peculiar in the composition is the entomocomplex of ferula on the highest site of Saridukon. The daily activity of pollinating insects was analysed.